AripiprazoleMontmorillonite: A New Organic–Inorganic Nanohybrid Material for Biomedical Applications. Issue 15 (21st February 2013) - Oh, Yeon‐Ji; Choi, Goeun; Choy, Young Bin; Park, Je Won; Park, Jung Hyun; Lee, Hwa Jeong; Yoon, Yeo Joon; Chang, Hee Chul; Choy, Jin‐Ho
Abstract Poor aqueous solubility and the unpleasant taste of aripiprazole (APZ) have been recurring problems, owing to its low bioavailability and low patient tolerance, respectively. Herein, we prepared a nanohybrid system that was based on a bentonite clay material, montmorillonite (MMT), which could both mask the taste and enhance the solubility of APZ (i.e., APZ‐MMT). To further improve the efficacy of this taste masking and drug solubility, APZ‐MMT was also coated with a cationic polymer, polyvinylacetal diethylamino acetate (AEA). In vitro dissolution tests at neutral pH showed that the amount of drug that was released from the AEA‐coated APZ‐MMT was greatly suppressed (<1 %) for the first 3 min, thus suggesting that AEA‐coated APZ‐MMT has strong potential for the taste masking of APZ. Notably, in simulated gastric juice at pH 1.2, the total percentage of APZ that was released within the first 2 h increased up to 95 % for AEA‐coated APZ‐MMT. Furthermore, this in vitro release profile was also similar to that of Abilify®, a commercially available medication. In vivo experiments by using Sprague–Dawley rats were also performed to compare the pharmacokinetics of AEA‐coated APZ‐MMT and Abilify®. AEA‐coated APZ‐MMT exhibited about 20 % higher systemic exposure of APZ and its metabolite, dehydro‐APZ, compared with Abilify®. Therefore, a new MMT‐based nanovehicle, which is coated with a cationic polymer, can act as a promising delivery system for both taste masking and for enhancing the bioavailability of APZ.